Hertzian elasticity and triggered swelling kinetics of poly(amino ester)-based gel beads with controlled hydrophilicity and functionality: A mild and convenient synthesis via dropwise freezing into cryogenic liquid - Ökten, Nur Sena; Çanakçı, Cahit Can; Orakdoğen, Narin (My University, 2019)
Poly(amino ester)-based homo- and co-polymeric gel beads were prepared via "dropwise freezing into cryogenic liquid" method and multi-responsive properties of the prepared spherical beads were confirmed by the pulsatile swelling kinetics and the stress-strain relationships based on Hertzian elasticity. Dual pH- and ionic strength-responsive homopolymeric PDMAEMA as well as copolymeric poly(hydroxyethyl methacrylate-co-dimethylaminoethyl methacrylate) P(HEMA-co-DMAEMA) gel beads crosslinked with diethyleneglycol dimethacrylate (DEGDMA) were prepared by aqueous phase crosslinking copolymerization at subzero temperature within the millimeter-sized frozen droplets in the paraffin oil as continuous phase. With this method, spherical ionic gel beads of sizes 2-5 mm could be synthesized without using a stabilizer. The successful synthesis of PDMAEMA and P(HEMA-co-DMAEMA) gel beads was confirmed by ATR-FTIR and SEM. Modulus of elasticity of cross-linked poly(amino ester)-based gel beads in swollen state was measured as a function of the bead diameter. The relationship between the compressive elastic force and corresponding deformation was obtained to compare the experimental results with theoretical-analytical formulations using the constitutive relations from Hertzian elasticity. The effective crosslink density of gel beads produced in the same synthesis batch increased as a function of increasing bead diameter, which was attributed to the formation conditions of the beads via frozen droplets of the pre-gel solution. The synthesis pathway used for the production of gel beads from methacrylate-based monomer with a polar tertiary amino group offered one-way control over material geometry to design soft and smart materials with controlled size and porosity.
Keywords: Hertzian Elasticity; Gel Beads; Hydroxyethyl Methacrylate; Dimethylaminoethyl Methacrylate; Swelling; Diffusion; Hertz Esnekliği; Jel Boncuklar; Hidroksietil Metakrilat; Dimetilaminoetil Metakrilat; Şişme; Yayılma